2015
DOI: 10.1121/1.4908568
|View full text |Cite
|
Sign up to set email alerts
|

Wind fence enclosures for infrasonic wind noise reduction

Abstract: A large porous wind fence enclosure has been built and tested to optimize wind noise reduction at infrasonic frequencies between 0.01 and 10 Hz to develop a technology that is simple and cost effective and improves upon the limitations of spatial filter arrays for detecting nuclear explosions, wind turbine infrasound, and other sources of infrasound. Wind noise is reduced by minimizing the sum of the wind noise generated by the turbulence and velocity gradients inside the fence and by the area-averaging the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The advantage of the proposed method is that the desired sound signal can be extracted from wind noise even when the sound signal is much lower than the wind noise. In addition, contrasting with existing WNR structures, e.g., large spatial filters (DeWolf et al, 2013) and wind fence enclosures (Abbott et al, 2015), the proposed method uses only a portable spherical microphone array, which is convenient for outdoor noise measurements. Finally, the proposed method is flexible and can be extended to spherical beamforming for future sound source localization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of the proposed method is that the desired sound signal can be extracted from wind noise even when the sound signal is much lower than the wind noise. In addition, contrasting with existing WNR structures, e.g., large spatial filters (DeWolf et al, 2013) and wind fence enclosures (Abbott et al, 2015), the proposed method uses only a portable spherical microphone array, which is convenient for outdoor noise measurements. Finally, the proposed method is flexible and can be extended to spherical beamforming for future sound source localization.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the rosette filters only produce reductions if the turbulence scale is smaller than the diameter of the rosette, and the cylindrical barrier has large reductions only when the scale size of the turbulence is smaller than the height of the barrier. Abbott et al (2015) optimized the WNR of a porous wind fence enclosure which is 2.9 m high and has a diameter of 5.0 m, and found that the best reduction was achieved with a surface porosity between 40% and 55%, supplemented by a secondary windscreen.…”
Section: Introductionmentioning
confidence: 99%
“…To quantitatively examine the wind noise reduction performance of the windscreens, the Wind Noise Reduction (WNR) are defined as (Abbott et al, 2015)…”
Section: Simulation Modelmentioning
confidence: 99%
“…Similar to porous microphone windscreens, spatial filters and wind fences with different porosity were used to attenuate the infrasonic wind noise outdoors (Abbott et al, 2015;Hedlin and Raspet, 2003). Abbot and Raspet (2015) developed a calculation model to predict the wind noise below 50 Hz in a 2.9 m high and 5.0 m diameter wind fence, and showed that the low frequency wind noise is only due to turbulence-shear interaction in the undisturbed region while the higher frequency wind noise is due to a combination of the turbulence-turbulence and turbulence-shear interactions inside the enclosure and the turbulence interactions on the surface of the enclosure.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic turbulent eddies in the air flow produce low-frequency pressure fluctuations [1]. Especially when interacting with objects such as microphones, sound sources appear with a non-negligible power [2]. A problem thus arises when measuring wind turbine infrasound as it always co-occurs with wind-induced microphone noise in this frequency range.…”
Section: Introductionmentioning
confidence: 99%